Adjusting Inventories for Consolidated Statements . - Rushing, Reginald (The Accounting Review, 1965)
The article focuses on the problem of teaching consolidated statements. One of the difficulties of teaching consolidated statements has been the adjustments to be made for intercompany profit in inventory. This problem has been greater where minority interests were involved. The problem of teaching the elimination of intercompany profits is still complicated by the fact that the eliminations required are not the same if made for consolidated balance sheet statements only, as when made for consolidated income statements and balance sheets. Further differences are found in eliminations when the investment is carried on a cost basis as contrasted with the investment carried on an equity basis. The illustration used by the author is one for adjustments or eliminations where both consolidated balance sheets and income statements are involved, since this is assumed to be more difficult than the adjustments or eliminations when only balance sheets are to be consolidated. The author has found that an illustration of this type, where the varying eliminations can be seen in one place, gives the student a better understanding of the problem than piecemeal consideration of the problem.